Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
the answer is
X=1
-3(x-7)+2=20
-3x + 21 + 2 = 20
-3x + 23 = 20
-23. -23
-3x=-3
Divide by -3
X=1
X=1
-3(x-7)+2=20
-3x + 21 + 2 = 20
-3x + 23 = 20
-23. -23
-3x=-3
Divide by -3
X=1
Answer:
x=1
Step-by-step explanation:
First you will distribute it
U basically multiply the 3 by the X and the 7 here
-3 x (x = -3x And the 7 becomes a 21
Then you add the 2
21 + 2 = 23
Then you add the -3
-3x + 23 =20
Then using the equation above you subtract 23 from both sides
(-3 + 23) - 23 = 20 - 23
Then you simplify it
-3x = -3
Then you divide them using the same term
-3
÷ -3
Then you simplfy it and you get
x=1
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.